Capreomycin-induced serum electrolyte abnormalities. Issue 5 (September 1970) - Holmes, A. M.; Hesling, C. M.; Wilson, T. M.
Abstract : Gross electrolyte disturbances including hypokalaemia, hypomagnesaemia, hypocalcaemia, and alkalosis have developed in tuberculous patients who were being treated with capreomycin. Similar abnormalities have also occurred when the drug gentamicin was used and were found to be due to secondary hyperaldosteronism. In this paper a detailed description of the changes induced by capreomycin is given. The evidence available strongly suggests a similar aetiology for the biochemical changes, but the precise pathophysiology is unknown. Caution should be exercised when capreomycin is used and the drug should be withdrawn if any of these abnormalities develop.